THE EFFECT OF PROVIDING BANANA HUMBLE MOL AND LIQUID ORGANIC FERTILIZER (POC) RICE WASHING ON THE GROWTH AND PRODUCTION OF PURPLE EGGPLANT (Solanum melongena L.) - Winata, Muhammad Adrian; Desi Sri Pasca Sari Sembiring; Tharmizi Hakim (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
Purple eggplant is an important vegetable crop in various cuisines, and the market demand for this crop is quite high. Fertilization is done as an effort to meet the needs of plants so that production goals can be achieved. This research was conducted at the office land of Pulo Brayan Bengkel Baru Urban Village, East Medan District, Deli Serdang Regency, North Sumatra with an altitude of ± 500 meters above sea level. This study used a Factorial Randomized Group Design (RAK) pattern. The treatment factor used in the study was the application of MOL bonggol pisang and POC rice washing water consisting of 4 levels of treatment and 3 repetitions. The first factor of MOL bonggol pisang is P0 = No Giving, P1 = 200 ml / water, P2 = 400 ml / water, P3 = 600 ml / water. The second factor is rice washing water POC, namely A0 = No Application, A1 = 150 ml / water, A2 = 300 ml / water, A3 = 450 ml / water. Observations of parameters in this study were plant height, number of productive branches, number of fruits, fruit weight per plant and fruit weight per plot. From this design, 16 treatment combinations were obtained and 3 repetitions were carried out, so that 48 experimental units were obtained in the study. The results showed that the treatment of MOL banana pomace strongly influenced all research parameters, the optimal concentration of MOL banana pomace was 400 ml / water. POC rice washing water is very influential on all research parameters, the optimal concentration of POC rice washing water is 450 ml / water. The purpose of this study was to determine the effect of banana stem moles and washing water POC on the growth and production of purple eggplant plants.